Von Willebrand factor in the outcome of temporal arteritis. Issue 12 (December 1996) - Cid, M C; Monteagudo, J; Oristrell, J; Vilaseca, J; Pallarés, L; Cervera, R; Font, C; Font, J; Ingelmo, M; Urbano-Márquez, A
Abstract : OBJECTIVE: To determine fluctuation in circulating von Willebrand factor (vWF) in the outcome of patients with temporal arteritis. METHODS: Plasma vWF antigen concentrations were measured in 65 patients with biopsy proven temporal arteritis at different disease activity stages, in 12 with isolated polymyalgia rheumatica, and in 16 controls. Fourteen temporal arteritis patients underwent serial determinations during the course of their disease. RESULTS: vWF concentrations were significantly raised in temporal arteritis (mean 220 [arbitrary units], range 96 to 720) and in polymyalgia rheumatica (mean 196, range 103 to 266) compared with healthy controls (mean 98, range 75 to 137) (P < 0.05). Although vWF values tended to be higher in temporal arteritis, no significant differences were found between temporal arteritis and polymyalgia rheumatica patients nor between temporal arteritis patients with ischaemic complications (mean 269, range 130 to 720) and those who presented with polymyalgia rheumatica or constitutional symptoms only (mean 179, range 140 to 220). The highest levels were obtained in patients with associated, mainly infectious, diseases (mean 631, range 240 to 1680). Raised vWF values found in active temporal arteritis patients (mean 220, range 96 to 720) persisted within the first two years after the beginning of treatment (mean 244, range 102 to 510) but tended to normalise in patients in long term remission (mean 143, range 50 to 260). CONCLUSIONS: Persistent elevation of vWF during early remission of temporal arteritis might represent an endothelial activation status induced by a remaining inflammatory microenvironment rather than a marker of endothelial cell injury. In long term remission, decreasing vWF concentrations might reflect progression of inflammatory lesions to a healing stage.